Instructional Quality and Student Learning in Higher Education: Evidence from Developmental Algebra Courses. (1st January 2016) - Chingos, Matthew M.
Abstract : Little is known about the importance of instructional quality in American higher education because few recent studies have had access to direct measures of student learning that are comparable across sections of the same course. Using data from two developmental algebra courses at a large community college, I found that student learning varies systematically across instructors and was correlated with observed instructor characteristics including education, full-time status, and experience. Instructors appeared to have effects on student learning beyond their impact on course completion rates. A variety of robustness checks suggested that these results do not appear to be driven by nonrandom matching of students and instructors based on unobserved characteristics or censoring of the dependent variable due to students who dropped the course before the final exam.